2019
DOI: 10.1101/686709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress- and pathway-specific impacts of impaired jasmonoyl-isoleucine (JA-Ile) catabolism on defense signaling and biotic stress resistance in Arabidopsis

Abstract: 20 21 Jasmonate (JA) synthesis and signaling are essential for plant defense upregulation upon 22 46 47 48 identification of jasmonoyl-isoleucine (JA-Ile) as the critical bioactive form in 2007 (Chini et 54 al. 2007; Thines et al. 2007), many derivatives of jasmonic acid (JA) were described, resulting 55 from hydroxylation, conjugation to sugars (Miersch et al. 2008), amino acids or amino 56 cyclopropane carboxylic acid, sulfation (Gidda et al. 2003), decarboxylation and many more 57 (Wasternack and Song 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…Our observation of decreased S. frugiperda growth due to ZmCYP94B1 expression silencing is different from what was observed with Arabidopsis, where S. littoralis larval growth on a cyp94B1 cyp94B3 cyp94C1 triple mutant was improved relative to wildtype plants (Marquis et al, 2020). The faster caterpillar weight gain on this triple mutant was ascribed to the higher expression of JAZ repressor proteins, which negatively regulate defense-induced genes, in the triple mutant.…”
Section: List Of Supplementary Materialscontrasting
confidence: 99%
See 4 more Smart Citations
“…Our observation of decreased S. frugiperda growth due to ZmCYP94B1 expression silencing is different from what was observed with Arabidopsis, where S. littoralis larval growth on a cyp94B1 cyp94B3 cyp94C1 triple mutant was improved relative to wildtype plants (Marquis et al, 2020). The faster caterpillar weight gain on this triple mutant was ascribed to the higher expression of JAZ repressor proteins, which negatively regulate defense-induced genes, in the triple mutant.…”
Section: List Of Supplementary Materialscontrasting
confidence: 99%
“…A phylogenetic analysis (Figure 7) showed that ZmJIH1 (GRMZM2G090779) is the closest maize homolog of Nicotiana attenuata JIH1 (Woldemariam et al, 2012), rice AH8 (Hazman et al, 2019), and Arabidopsis IAR3 (Marquis et al, 2020), which have previously been identified as JA-Ile hydrolases. We cloned a fragment of this gene into SCMV-CS3 for VIGS experiments.…”
Section: List Of Supplementary Materialsmentioning
confidence: 99%
See 3 more Smart Citations